Climate footprint of industry-sponsored in-human clinical trials: life cycle assessments of clinical trials spanning multiple phases and disease areas - Michael Collins; Thomas Costelloe; Jason Keith LaRoche; Rodrigo Alvarenga; Wouter De Soete; Jeremy Faludi; Kristel Rens; Jason Lanier; Annemie Chiau; Hugh Whetherly (BMJ Open)
Objective This study aims to calculate the global warming potential, in carbon dioxide (CO2) equivalent emissions, from all in-scope activities involved in phase 1, 2, 3 and 4 clinical trials spanning multiple disease areas.Design The study design involved a retrospective analysis of completed clinical trials.Setting Select set of seven clinical trials conducted between 2018 and 2023 and sponsored by Johnson & Johnson Innovative Medicine: TMC114FD1HTX1002, 77242113PSO2001, 42756493BLC2002, 54767414MMY3012, VAC18193RSV3006, R092670PSY3016 and 28431754DIA4032Participants While participants and the public were involved in all seven trials, the life cycle assessments (LCAs) were performed as an independent retrospective analysis after the clinical trials were completed. As a retrospective analysis, we leveraged clinical trial documentation and interviews with the sponsor trial staff and trial site staff. None of the participating trial subjects were involved specifically in the LCA analysis, nor was any personal identifying information from the trial subjects collected or shared.The underlying clinical trials were performed in accordance with the Declaration of Helsinki and Guidelines for Good Pharmacoepidemiology Practice. All participating investigators were required to obtain full governing board approval for conducting research involving humans. Sponsor approval and continuing review were obtained through the appropriate Institutional Review Board/Ethics Committee (IRB) and Health Authority channels. For academic investigative sites that did not receive authorisation to use the central IRB, full board approval was obtained from their respective governing IRBs, and documentation of approval was submitted to Johnson & Johnson Innovative Medicine, LLC, before the site’s participation and initiation of any trial procedures. All registry participants provided written informed consent and authorisation before participating.Primary outcome measure Primary outcome measure CO2 equivalents (CO2e) for in-scope clinical trial activities calculated according to Intergovernmental Panel on Climate Change 2021 impact assessment methodology.Results The TMC114FD1HTX1002 phase 1 trial was the smallest trial both in terms of number of patients (39) and sites (1) and had the smallest emissions at 17 648 kgCO2e. The 54767414MMY3012 phase 3 trial was not the largest trial in terms of number of participating patients (517) but had the largest number of participating sites (129) and had the largest emissions at 3 107 436 kg CO2e. Across all seven trials analysed, the mean emissions per patient were 3260 kg CO2e. When the overall trial footprints are broken down by phase, the phase 2 mean per patient was 5722 kg CO2e and the phase 3 mean per patient emissions were 2499 kg CO2e. The five largest contributors of greenhouse gas (GHG) emissions were drug product (50% mean), patient travel (10% mean), travel for on-site monitoring visits (10% mean), collection and processing of laboratory samples (9% mean) and sponsor staff commuting (6% mean). Patient travel was the only consistent GHG hotspot across all seven trials, as other hotspots appeared intermittently in some trials but not others based on variations in trial design. Across the multisite phase 2, 3 and 4 trials we analysed, a combination of the observed five largest contributors to GHG emissions were responsible for no less than 79% of GHG emissions for any one trial.Conclusions Based on our LCAs of seven clinical trials spanning all four phases of development and multiple disease areas, there are five activities that drive no less than 79% of the average clinical trial’s GHG footprint. These are drug product manufacture, packaging, and distribution; patient travel; on-site monitoring visit travel; the collection, transport and processing of laboratory samples; and sponsor staff commuting between their homes and the office. Understanding the activities that drive GHG emissions in clinical trials can both guide trial designers in avoiding or minimising reliance on these activities when designing new trials and guide trial sponsors in taking targeted actions to reduce GHG emissions from these activities where their use cannot be avoided.Trial registration number TMC114FD1HTX1002 (ClinicalTrials.gov: NCT04208061), 77242113PSO2001 (ClinicalTrials.gov: NCT05364554), 42756493BLC2002 (ClinicalTrials.gov: NCT03473743), 54767414MMY3012 (ClinicalTrials.gov: NCT03277105), VAC18193RSV3006 (ClinicalTrials.gov: NCT05070546), R092670PSY3016 (ClinicalTrials.gov: NCT04072575) and 28431754DIA4032 (ClinicalTrials.gov: NCT04288778).